1972
DOI: 10.1002/chin.197227126
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: KERNMAGNETISCHE RESONANZUNTERSUCHUNGEN UND SELBSTDIFFUSION AN KRITISCHEN PUNKTEN IN FLUIDEN SYST.

Abstract: Es wird ein Überblick über die bisher vorliegenden Kernresonanzuntersuchungen in der Nähe kritischer Zustände in fluiden, überwiegend organischen Einund Zweistoffsystemen ( ;z.B. Methanol‐Csz, n‐Heptan‐Perfluormethylcyclohexan, Triäthylamin‐Wasser) gegeben.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

1977
1977
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 1 publication
3
9
0
Order By: Relevance
“…Our calculations of the SDC within the critical mixing region have been done with a larger number of iterations (up to 104) and the closest approach to the experimental critical temperature was 2.0_+ 0.3 K. No temperature-dependent anomalous behaviour of the SDC occurred in the critical region. This is in accordance with experiment on other partially miscible systems [5,25]. Short time oscillations of the MSD of the Ne/Kr system have have not been found--unlike in the investigations on the CHJCF 4 system [I]--the MSD of neither component converged in fewer than 103 iterations.…”
Section: Self-diffusion Coefficients Of the Mixturesupporting
confidence: 88%
See 2 more Smart Citations
“…Our calculations of the SDC within the critical mixing region have been done with a larger number of iterations (up to 104) and the closest approach to the experimental critical temperature was 2.0_+ 0.3 K. No temperature-dependent anomalous behaviour of the SDC occurred in the critical region. This is in accordance with experiment on other partially miscible systems [5,25]. Short time oscillations of the MSD of the Ne/Kr system have have not been found--unlike in the investigations on the CHJCF 4 system [I]--the MSD of neither component converged in fewer than 103 iterations.…”
Section: Self-diffusion Coefficients Of the Mixturesupporting
confidence: 88%
“…This is particularly useful in studying the critical region, since we expect a critical mixture to show cooperative phenomena which should be reflected in the radial distribution functions [5]. Though the periodic boundary conditions and the limited number of particles make it impossible to simulate phase separations or precisely a critical state, molecular aggregation, which is known to occur even 5-15 K away from the critical temperature [6], should be indicated.…”
Section: Mp I Gmentioning
confidence: 99%
See 1 more Smart Citation
“…[1,2]. Reported NMR studies on this field are focused on the spinecho measurements of self diffusion and on the determination of the spin-lattice relaxation time T, [3]. There has been noticed a weak influence of the critical state on the NMR signals.…”
Section: Introductionmentioning
confidence: 99%
“…NMR studies by Krynicki et al 13 and by Etesse et al 14 stand in contradiction to the finding of Duffield and Harris and found no anomaly in the behavior of D. Although the values of D given in the two cited papers were measured by the same technique, there is a 40% systematic difference between the two studies. In general, most of the experimental results which were reviewed by Hamann et al 15 indicate that there is no anomaly in the behavior of D in the critical region of systems such as CH 4 , C 2 H 4 , CClF 3 , and SF 6 . Molecular-dynamics ͑MD͒ simulation technique can provide invaluable information on the correlation between the thermodynamic, structural, and spectroscopic properties of fluids on a fundamental molecular level.…”
Section: Introductionmentioning
confidence: 94%